TECHNOLOGY MANAGEMENT IN EDUCATION AND TRAINING: A THEORETICAL CONCEPT - Fauzi, Reza; Khusni, Khusni Khusni; Zaqiah, Qiqi Yuliati (Tatar Pasundan: Jurnal Diklat Keagamaan, 2023)
This study attempts to get a general understanding of technology management in training and education. This research employs a qualitative approach with the literature method. The findings indicated that management actions serve as the key support for educational technology to provide outcomes that are consistent with the goals. The successful management of educational technology by human resources within educational institutions is essential to its implementation in educational institutions. If there is a trained workforce in the area of educational technology who can 1) design learning processes and resources, with the scope of work including designing learning systems, message design, learning strategies, and learner characteristics, then educational technology can be developed and used properly; 2) create educational materials and methods, such as the advancement of print technology, audiovisual technology, computer-based technology, and integrated technology; 3) use learning procedures and tools, such as learning media, educational innovation dissemination, and rules and guidelines adoption governing education and training; 4) manage learning resources and processes with project management, and education-training management information systems, etc.; and 5) evaluate problem analysis, benchmark reference measurement, the formative and summative assessment included in the evaluation.Â Keywords: Management; Educational Technology; Education; Learning; Training